Social singing, culture and health: interdisciplinary insights from the CHIME project for perinatal mental health in The Gambia. (16th February 2022) - Stewart, Lauren; McConnell, Bonnie B; Darboe, Buba; Glover, Vivette; Huma, Hajara B; Sanfilippo, Katie Rose M; Cross, Ian; Ceesay, Hassoum; Ramchandani, Paul; Cornelius, Victoria
Summary: Arts in Health initiatives and interventions to support health have emerged from and been applied to mainly WEIRD (Western, Educated, Industrialized, Rich and Democratic) contexts. This overlooks the rich cultural traditions that exist across the globe, where community groups often make prolific use of participatory song and dance as a part of ceremonies, ritual and gatherings in everyday life. Here, we argue that these practices can provide a valuable starting point for the co-development of health interventions, illustrated by the CHIME project for perinatal mental health in The Gambia, which worked with local Kanyeleng groups (female fertility societies) to design and evaluate a brief intervention to support maternal mental health through social singing. Here, we use the project as a lens through which to highlight the value of co-creation, cultural embeddedness and partnership building in global health research.